Family dynamics and health attitudes - Witham, Rachel Yvonne (Kansas State University, 2011)
The present study examined adolescents’ perceptions of their caregivers’ parenting style as well as their physical activity participation, motivation, and attitudes. High school students completed questionnaires regarding their physical activity participation, motivation, and attitudes, and they assessed both their male and female caregivers’ parenting style. Results indicated that for males, a permissive parenting style was related to more physical activity participation and that males favor physical activity that features long and hard training and as a way to stay healthy and fit. An authoritative parenting style was related to higher rates of physical activity for females, and their attitudes focused on social aspects of physical activity as well as a release of tension. For both genders, identified regulation was associated with higher rates of physical activity, indicating that higher levels of self-determined motivation are important for promoting active behaviors. Cross-gender relationships between caregiver and child emerged and social and gender norms seemed to influence parenting style and attitudes specific to gender. Additional results and implications are discussed.
Keywords: Parenting Style; Physical Activity; Adolescents; Motivation; Attitude; Health Education (0680); Individual & Family Studies (0628); Public Health (0573)